2006
DOI: 10.1128/iai.00261-06
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis galEIs Involved in Lipopolysaccharide O-Antigen Synthesis and Biofilm Formation

Abstract: Porphyromonas gingivalis is a crucial component of complex plaque biofilms that form in the oral cavity, resulting in the progression of periodontal disease. To elucidate the mechanism of periodontal biofilm formation, we analyzed the involvement of several genes related to the synthesis of polysaccharides in P. gingivalis. Gene knockout P. gingivalis mutants were constructed by insertion of an ermF-ermAM cassette; among these mutants, the galE mutant showed some characteristic phenotypes involved in the loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 40 publications
8
72
2
Order By: Relevance
“…had been reported previously for another strain (21). This effect is not due to a change in the transcription of PG0121 downstream in the operon (Fig.…”
Section: Figmentioning
confidence: 49%
See 2 more Smart Citations
“…had been reported previously for another strain (21). This effect is not due to a change in the transcription of PG0121 downstream in the operon (Fig.…”
Section: Figmentioning
confidence: 49%
“…We previously reported that deletion of the HU protein PG0121, which is encoded at the 3= end of the capsule locus, has altered polysaccharide content and that a variety of loci are differentially expressed in the PG0121 deletion mutant, including genes in known polysaccharide synthesis loci, including the APS synthesis locus PG1135-PG1142 (25,26). It has also been reported that deletion of PG0106 in P. gingivalis strain 33277, the first gene in the K-antigen operon, yields a strain with an altered LPS profile on silver-stained gels of purified LPS (21). To examine the possibility that the structure of the LPS molecules is also modulated by the 77bpIR element, proteinase K-digested whole-cell lysates were compared for LPS profile by silver ammonia-stained SDS-PAGE gels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UDP-galactose is required in multiple steps within the LPS synthesis pathway. This specific mutant has been documented (59) and is known to have a shortened O-antigen chain as a result but was still viable. In light of this experimental validation of our modeling approach, it will be useful to experimentally test the other potential knockouts listed in Table 3.…”
Section: Vol 191 2009 Metabolic Network Model Of a Human Oral Pathomentioning
confidence: 99%
“…The UDPG4E reaction is linked to the galE gene, producing a UDP-glucose 4-epimerase. The galE mutants are known to have modified lipid A molecules (59). The pathway culminates in the production of lps_PG1, lps_PG2, and lps_PG3 molecules, which refer to the PG1690, PG1450, and PG1435 lipid A structures, respectively.…”
mentioning
confidence: 99%